2017
DOI: 10.1093/mnras/stx057
|View full text |Cite
|
Sign up to set email alerts
|

The ASAS-SN Bright Supernova Catalog – II. 2015

Abstract: This manuscript presents information for all supernovae discovered by the All-Sky Automated Survey for SuperNovae (ASAS-SN) during 2015, its second full year of operations. The same information is presented for bright (m V ≤ 17), spectroscopically confirmed supernovae discovered by other sources in 2015. As with the first ASAS-SN bright supernova catalogue, we also present redshifts and near-ultraviolet through infrared magnitudes for all supernova host galaxies in both samples. Combined with our previous cata… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…The fraction of discoveries belonging to each of these classes is in agreement with the results from Li et al (2011) for a magnitude-limited survey, as shown in Figure 3. 38 Figure 3 also shows the relative rate of SNe found by ASAS-SN (Holoien et al 2017a(Holoien et al , 2017b(Holoien et al , 2017c(Holoien et al , 2019, which, like the ZTF BTS and unlike LOSS, does not target specific galaxies when searching for transients. 39 Both ZTF and ASAS-SN find a higher fraction of SNe II than LOSS, although these estimates all agree to within the uncertainties.…”
Section: Classificationsmentioning
confidence: 99%
“…The fraction of discoveries belonging to each of these classes is in agreement with the results from Li et al (2011) for a magnitude-limited survey, as shown in Figure 3. 38 Figure 3 also shows the relative rate of SNe found by ASAS-SN (Holoien et al 2017a(Holoien et al , 2017b(Holoien et al , 2017c(Holoien et al , 2019, which, like the ZTF BTS and unlike LOSS, does not target specific galaxies when searching for transients. 39 Both ZTF and ASAS-SN find a higher fraction of SNe II than LOSS, although these estimates all agree to within the uncertainties.…”
Section: Classificationsmentioning
confidence: 99%
“…During O1 and O2, astronomers found and followed-up numerous CCSNe in the nearby universe. Based on the information from Astronomical Telegrams [36] and supernova catalogs (ASAS-SN [37][38][39][40], DLT40 [41], Gaia [42,43], ASRAS [44], TNS [45], OSC [46], CBAT [47]), we found 9 supernovae of interest.…”
Section: Targeted Core-collapse Supernovaementioning
confidence: 99%
“…SNe Ia are intrinsically luminous (Riess et al, 2016), thus, even with modest aperture telescopes SNe Ia can be discovered over large volumes; indeed, the All Sky Survey for Supernova (ASAS-SN; Shappee et al, 2014a) uses telescopes with only a 14 cm aperture to discover a total of 242 confirmed SNe, of which 183 were SN Ia (76%) over its first 18 months of dual-hemisphere operations (01 May 2014 to 31 December 2015) alone within m V < 17 (Holoien et al, 2017a) 1 . Their intrinsic luminosity also permits their discovery at significant redshift; the previous most distant SN Ia SN UDS10Wil at z=1.914, which was discovered in the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS, PI: Faber & Ferguson; see Jones et al, 2013, for details), was recently replaced with another 15 in the range from 1.9< z <2.3 presented in Riess et al (2017).…”
Section: Supernovae Iamentioning
confidence: 99%
“…From inspection of Figure 4b, the number of SNe Ia discovered per annum fluctuates widely, but, in general, the numbers do not trend strongly with the onset of all-sky monitoring programs (albeit these programs permit unprecedented early detection; e.g., Figure 2). Analyses of yearly rates over the next few years, however, will be more informative with programs like ASAS-SN having become dramatically more efficient (e.g., Holoien et al, 2017b).…”
Section: The 'Local' Sample In Contextmentioning
confidence: 99%
See 1 more Smart Citation